Pediatric anorexia nervosa: the impact of the COVID-19 pandemic - Tavares, Mónica (2022)
Introduction: Social distancing associated with the COVID-19 pandemic carried significant psychological implications and might be linked to an increased incidence of anorexia nervosa (AN) in adolescents. This study sought to assess the impact of the pandemic on the incidence, demographics, and clinical severity of AN. Methods: This was a retrospective cross-sectional study of adolescents with AN followed by the Multidisciplinary Group of Eating Disorders of a Portuguese tertiary hospital between January 1, 2017 and May 31, 2022. Adolescents were divided into two groups according to the beginning of their follow-up: pre- or post-pandemic (cut-off date, March 2, 2020). Demographic features, minimum body mass index (BMI) z-score, arm and abdominal circumference on admission, time of symptom onset, fat-free mass percentage by bioimpedance analysis, time to referral, presence of pericardial effusion, and number of hospital admissions were assessed and compared between groups. Results: A total of 217 patients with AN were identified, 57 of whom pre- and 160 post-pandemic. The average number of new cases per month in the post-pandemic period increased significantly compared to the pre-pandemic period (5.89 vs. 1.55; p=0,005), with a non-significant increase in male cases (p=0.127). No significant differences were found between groups regarding minimum BMI z-score, arm or abdominal circumference, age at diagnosis, or time between symptom onset and referral to AN follow-up. Discussion: The incidence of AN increased by more than threefold during the pandemic, with a slightly higher number of male cases. Despite this increase, no association was found with greater clinical severity or delay in patient referral. Conclusion: Despite changes in the dynamics of health services due to the pandemic, these did not translate into a delay in the referral or follow-up of patients with AN.